Tax Rates and Corporate Decision-making - Graham, John R.; Hanlon, Michelle; Shevlin, Terry; Shroff, Nemit (Review of Financial Studies, 2017)
We survey companies and find that many use incorrect tax rate inputs into important corporate decisions. Specifically, many companies use an average tax rate (the GAAP effective tax rate, ETR) to evaluate incremental decisions, rather than using the theoretically correct marginal tax rate. We find evidence consistent with behavioral biases (heuristics, salience) and managers' educational backgrounds affecting these choices. We estimate the economic consequences of using the theoretically incorrect tax rate and find that using the ETR for capital structure decisions leads to suboptimal leverage choices and using the ETR in investment decisions makes firms less responsive to investment opportunities.